2011
DOI: 10.1371/journal.pone.0028351
|View full text |Cite
|
Sign up to set email alerts
|

Complex c-di-GMP Signaling Networks Mediate Transition between Virulence Properties and Biofilm Formation in Salmonella enterica Serovar Typhimurium

Abstract: Upon Salmonella enterica serovar Typhimurium infection of the gut, an early line of defense is the gastrointestinal epithelium which senses the pathogen and intrusion along the epithelial barrier is one of the first events towards disease. Recently, we showed that high intracellular amounts of the secondary messenger c-di-GMP in S. typhimurium inhibited invasion and abolished induction of a pro-inflammatory immune response in the colonic epithelial cell line HT-29 suggesting regulation of transition between bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
119
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 66 publications
3
119
0
2
Order By: Relevance
“…CsgD in turn directly activates the csgBAC operon, encoding the subunits of curli fimbriae, as well as adrA, encoding the DGC required for activation of cellulose biosynthesis (309). Although CsgD does not appear to affect flagellar motility in S. enterica in a major way, it does affect the expression of distinct genes of the flagellar regulon (309,310) and is involved in flagellum-mediated stimulation of the innate immune response (311).…”
Section: Fig 10mentioning
confidence: 99%
See 3 more Smart Citations
“…CsgD in turn directly activates the csgBAC operon, encoding the subunits of curli fimbriae, as well as adrA, encoding the DGC required for activation of cellulose biosynthesis (309). Although CsgD does not appear to affect flagellar motility in S. enterica in a major way, it does affect the expression of distinct genes of the flagellar regulon (309,310) and is involved in flagellum-mediated stimulation of the innate immune response (311).…”
Section: Fig 10mentioning
confidence: 99%
“…Genetic screens demonstrated that c-di-GMP signaling pathways affect virulence in numerous animal and plant pathogens (7,183,(203)(204)(205)311).…”
Section: Cyclic Di-gmp and Virulencementioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15][16] Several major human pathogens, including Pseudomonas aeruginosa, Salmonella typhimurium, and Vibrio cholerae, possess numerous c-di-GMP-metabolizing proteins, and some studies confirmed the correlation of c-di-GMP-mediated signaling with biofilm formation. [17][18][19] Furthermore, modulation of c-di-GMP signaling by environmental changes has also been linked with the dispersion of cells from established biofilms. [20][21][22] Therefore, drugs able to inhibit c-di-GMP synthesis are promising candidates for new anti-microbial agents with anti-biofilm activity.…”
mentioning
confidence: 99%